1993
DOI: 10.1002/ejsp.2420230302
|View full text |Cite
|
Sign up to set email alerts
|

Attribution in conversational context: Effect of mutual knowledge on explanation‐giving

Abstract: (Hilton and Slugoski, 1986), that the common sense criterion of causality is that of an 'abnormal condition' rather than constant conjunction as instantiated in the A N 0 V A model of causal attribution (Kelley, 1967(Kelley, , 1973.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 39 publications
1
33
0
1
Order By: Relevance
“…This maxim encourages the provision of information that is new to the recipient and discourages the reiteration of information that the recipient already has. Consistent with the maxim of quantity, Slugoski, Lalljee, Lamb, and Ginsburg (1993) found that participants who were led to believe that their conversational partner shared only dispositional information about a target provided more situational explanations for the target's behavior. In contrast, those who believed that their partner shared only information about the situational background of the target gave somewhat more dispositional explanations.…”
Section: A Norenzayan and N Schwarzsupporting
confidence: 56%
See 2 more Smart Citations
“…This maxim encourages the provision of information that is new to the recipient and discourages the reiteration of information that the recipient already has. Consistent with the maxim of quantity, Slugoski, Lalljee, Lamb, and Ginsburg (1993) found that participants who were led to believe that their conversational partner shared only dispositional information about a target provided more situational explanations for the target's behavior. In contrast, those who believed that their partner shared only information about the situational background of the target gave somewhat more dispositional explanations.…”
Section: A Norenzayan and N Schwarzsupporting
confidence: 56%
“…Kelley, 1967), is in fact a process which is embedded in the social and communicative context in which it occurs (Hilton, 1990;Hilton & Slugoski, 1986;Slugoski, et al, 1993). More generally, our ®ndings contribute to the conclusion that the communicative context systematically aects social judgment and reasoning, and that participants bring the tacit assumptions that govern the conduct of conversation in daily life to the research situation (see Hilton, 1995;Kihlstrom, 1995;Schwarz, 1994Schwarz, , 1996.…”
Section: Participants Tailor Attributions 1017mentioning
confidence: 56%
See 1 more Smart Citation
“…and preference the inclusion of this information in their message (e.g., Grice, 1975;Lyons & Kashima, 2003;Slugoski, Lalljee, Lamb, & Ginsburg, 1993). This would suggest that in stereotyperelevant communication, it is the stereotype-inconsistent information (information less consistent with the shared stereotype) that is more likely to be communicated-an explanation that is at odds with the widespread stereotype consistency bias in communication.…”
mentioning
confidence: 99%
“…Several scholars studied how this initial model imparts on communication, namely because it can easily be manipulated. For instance, Slugoski, Lalljee, Lamb & Ginsburg (1993) pretended to the subjects that their (fake) partner has or not received the same information. They observed that the subjects adapt to their partner by focusing the explanation on the items that (s)he is supposed to ignore.…”
Section: Mutual Modeling In Collaborative Taskmentioning
confidence: 99%